1998
DOI: 10.1002/(sici)1098-2264(199812)23:4<307::aid-gcc5>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of chromosomal imbalances in gastric adenocarcinoma revealed amplified protooncogenes MYCN , MET , WNT2 , and ERBB2

Abstract: Gastric adenocarcinoma is a malignant tumor with a high incidence and a low survival rate. In order to identify genetic alterations associated with this tumor, we screened 23 gastric adenocarcinomas for recurrent chromosomal imbalances by using comparative genomic hybridization (CGH). The most common gains of chromosomal material were found on chromosome arms 20q (10 cases), 16p (7 cases), and 1q (4 cases) and on chromosome 11 (4 cases). Losses were observed on chromosome arms 4q, 5q, 9p, and 21q (3 cases each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 50 publications
7
60
1
Order By: Relevance
“…The receptor tyrosine kinase MET is considered one such potential target in cancer, and several MET-TKIs are currently undergoing clinical trials in humans. Amplification of MET is often responsible for activation of MET signaling, with such amplification occurring frequently in gastric cancer (4)(5)(6). We have now shown that crizotinib exerted a marked antitumor action in gastric cancer cells with MET amplification.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The receptor tyrosine kinase MET is considered one such potential target in cancer, and several MET-TKIs are currently undergoing clinical trials in humans. Amplification of MET is often responsible for activation of MET signaling, with such amplification occurring frequently in gastric cancer (4)(5)(6). We have now shown that crizotinib exerted a marked antitumor action in gastric cancer cells with MET amplification.…”
Section: Discussionmentioning
confidence: 85%
“…Substantial advances in the development of molecularly targeted therapies for gastric cancer have been achieved in recent years (3). Amplification of the proto-oncogene MET is a frequent molecular abnormality in gastric cancer (4)(5)(6), and a MET-tyrosine kinase inhibitor (TKI) has been shown to induce apoptosis in gastric cancer cells with MET amplification (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous CGH studies of adenocarcinomas of the stomach and the gastroesophageal junction have revealed gain on 22q in a low frequency (7,30,31). In addition, colorectal and gastric carcinomas frequently have loss of heterozygosity on chromosome 22q, suggesting that inactivation of tumor suppressor genes on 22q participates in the tumor development (32).…”
Section: Discussionmentioning
confidence: 99%
“…MYC has been implicated in many types of human cancer, and it is overexpressed in a subset of breast cancers (33). Although MET and MYC loci are coamplified in some gastric cancers (34,35), it is not known whether MET and MYC are cooverexpressed or whether these genes cooperate in the genesis of breast cancer.…”
Section: Overexpression Of Met Via Retroviral Transduction In Primarymentioning
confidence: 99%